Evaluation of enhanced pain management programs for patients undergoing surgery for severe knee osteoarthritis: a retrospective study - Peng Liu; Jiabing Li; Weimin Liang; Xiao Yang; Jiang Hu; Chongxin Huang; Ji Zhou (Annals of Medicine)
Background Surgical intervention is a primary treatment for advanced knee osteoarthritis (OA), yet effective postoperative pain management remains suboptimal. This study aimed to evaluate the clinical outcomes of different postoperative analgesic protocols to inform optimized perioperative pain strategies.Methods A retrospective analysis was conducted on 714 patients with knee OA who underwent total knee arthroplasty (TKA, n = 551), unicompartmental knee arthroplasty (UKA, n = 92), or high tibial osteotomy (HTO, n = 71). Patients were categorized into three groups (A, B, C) based on the postoperative analgesic regimen. Clinical parameters, including visual analogue scale (VAS) scores, knee range of motion (ROM), Hospital for Special Surgery (HSS) scores, emotional state, quadriceps strength, complication rates, and length of hospital stay, were compared. Statistical analyses were performed using factorial ANOVA.Results Significant differences in VAS scores at 24 h (static), 72 h (static), and 24 h (dynamic), ROM at 72 h, and HSS scores at 3 months were identified among groups, surgical procedures, and their interactions (p < 0.05). Differences in ROM at 24 h and HSS scores at 6 months were noted between groups and procedures, respectively (p < 0.05). VAS scores at 72 h (dynamic) also varied significantly by interaction effects (p < 0.05). Emotional status, quadriceps strength, and hospital stay length differed significantly between groups or procedures (p < 0.05). Complication rates were lower in Group C (22.03%) compared to Group A (46.61%) and Group B (26.45%) (p < 0.05).Conclusion Optimized perioperative analgesic protocols are associated with improved pain control, enhanced functional recovery, and reduced complication rates in knee osteoarthritis surgery. Further validation through prospective, multicenter studies is recommended.